Strontium isotopes as tracers for water-rocks interactions of groundwater to delineate iodine enrichment in aquifer of Datong Basin, northern China - Qian, Kun; Sun, Haowei; Li, Junxia; Xie, Xianjun (Applied geochemistry, 2023)
Groundwater iodine has direct importance for human dietary iodine intake in areas where drinking water is of groundwater origin. Iodine affected aquifer system in Datong Basin of North China was studied with a focus on strontium isotopes and major ion chemistry, in order to estimate the controlling hydrological and geochemical processes. The data revealed a rather complicated mixing pattern of various groundwater source end-members that were subject to different water-rock interactions, such as silicate weathering, evaporite and carbonate dissolution. Groundwater from the recharge area of east margin was characteristic by 87Sr/86Sr ratios higher than 0.71643, which implied the silicate weathering process. Groundwater from the discharge area and west margin might be originated from evaporite and carbonate dissolution processes with low 87Sr/86Sr ratios. Mixing models of three end-members based on Sr isotope and contents reflected that the type of water-rock interactions shifted from silicate weathering towards evaporite dissolution along the groundwater flow path from east margin to basin center. Abundant iodine and natural organic matters (NOMs) were discovered in groundwater located at the discharge area with Sr isotopic values between 0.710 and 0.717, implying evaporite dissolution governing iodine and NOMs enrichment in groundwater. Silicate weathering process had negligible influence on iodine and NOMs enrichment in groundwater. While carbonate dissolution made negative contribution for iodine releasing to aqueous phases. The PHREEQC inverse modeling results illustrated that dissolution of halite, calcite, gypsum and kaolinite and cation exchange significantly changed chemical composition of groundwater along the groundwater paths from the two basin margins to central area. •Elevated iodine groundwater was found in Datong Basin.•Silicate weathering caused high 87Sr/86Sr values.•Evaporite and carbonate dissolution caused low 87Sr/86Sr values.•Evaporite dissolution governed iodine releasing to groundwater.•Iodine enrichment was related to NOMs by water-rock interaction.